Orange red copper-based halide luminescent material and preparation method thereof

The preparation of orange-red copper-based halide luminescent materials through low-temperature cooling crystallization method and anti-solvent method has solved the problems of high temperature, high pressure and high cost of existing red phosphors, and achieved non-toxic, low-cost, broadband emission orange-red light effect. In the field of solid state lighting.

CN119143786APending Publication Date: 2024-12-17BEIJING INST OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411203167.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing red phosphors require a high temperature and high pressure environment during the preparation process, which is costly and contains lead, which affects its stability and safety, making it difficult to meet the requirements of large-scale production and safety.

Method used

The orange-red copper-based halide luminescent material (molecular formula (TPP)2Cu4Br6·2DMSO) was prepared by low-temperature cooling crystallization method, and microcrystals were obtained by anti-solvent method to achieve mass production at room temperature.

Benefits of technology

It realizes non-toxic, low-cost, broadband emission, and high fluorescent quantum yield orange-red light emission, which is suitable for solid-state lighting, reducing production costs and improving the safety and stability of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143786A_ABST
    Figure CN119143786A_ABST
Patent Text Reader

Abstract

The invention relates to an orange red copper-based halide luminescent material and a preparation method thereof, and belongs to the technical field of luminescent materials. The molecular formula of the luminescent material is (TPP) 2Cu4Br6. 2DMSO, and the luminescent material belongs to a Pbcn space group in an orthorhombic system, presents broadband orange-red light emission under ultraviolet excitation, has the characteristics of no toxicity, broadband emission, high fluorescence quantum yield, low cost and the like, and shows a huge application prospect in the field of solid-state illumination. According to the method, a single crystal of the luminescent material is obtained by adopting a low-temperature cooling crystallization method, and a micro crystal of the luminescent material is obtained by adopting an anti-solvent method; the preparation method has the characteristics of simplicity in operation, short reaction time, suitability for batch production and the like, and is beneficial to popularization and application of the luminescent material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an orange-red copper-based halide luminescent material and a preparation method thereof, belonging to the technical field of luminescent materials. Background Art

[0002] White light-emitting diodes (WLED) have excellent properties such as high brightness, long life, energy saving and environmental protection. They developed rapidly in the late 20th century and gradually replaced traditional light sources such as incandescent lamps and fluorescent lamps. They are widely used in lighting and display fields and are called the fourth generation of lighting sources. The mainstream WLED produced commercially is excited by Y3A blue light chips made of indium gallium nitride (InGaN). l5 O 12 ∶Ce 3+ (YAG) yellow phosphor encapsulation, however, this type of device lacks red light components, resulting in a low color rendering index and a high color temperature, which affects the quality of WLED. Studies have shown that adding red phosphor has a significant effect on improving the color rendering index of WLED devices, reducing color temperature and widening the color gamut. Therefore, researchers are committed to developing red phosphors that can be excited by blue light chips and are suitable for WLED.

[0003] At present, the more mature red phosphors mainly include rare earth ion doped nitride system, sulfide system, tungstate molybdate system and lead system. However, these phosphors have the following problems: (1) The preparation process usually requires a high temperature and high pressure environment, and the synthesis conditions are harsh; (2) Rare earths are expensive, and the cost of large-scale production is high; (3) Lead ions are toxic and the stability of the lead system is poor, which restricts the further development of this type of phosphor.

[0004] Therefore, it is necessary to explore high-efficiency, non-toxic, and low-cost red light phosphors that can be prepared under milder conditions. Summary of the invention

[0005] In view of the defects of current red light-emitting materials, one of the purposes of the present invention is to provide an orange-red copper-based halide light-emitting material, which emits orange-red light under ultraviolet excitation, has the characteristics of non-toxicity, broadband emission, high fluorescence quantum yield and low cost, and shows great application prospects in the field of solid-state lighting.

[0006] The second object of the present invention is to provide a method for preparing an orange-red copper-based halide luminescent material, wherein the method adopts a low-temperature cooling crystallization method to obtain a single crystal of the luminescent material, and adopts an anti-solvent method to obtain a micron crystal of the luminescent material; the method has the characteristics of simple operation, short reaction time, and suitability for mass production, which is conducive to the promotion and application of the luminescent material.

[0007] To achieve the purpose of the present invention, the following technical solutions are provided.

[0008] An orange-red copper-based halide luminescent material, the molecular formula of which is (TPP)2Cu4Br6·2DMSO. The luminescent material belongs to the Pbcn space group in the orthorhombic system, has a band gap of 2.92 eV, an excitation spectrum with a peak wavelength at 370 nm, an emission spectrum showing broadband emission with a peak wavelength at 615 nm, a fluorescence quantum yield of 88.1%, and broadband orange-red light emission under ultraviolet excitation.

[0009] A method for preparing the orange-red copper-based halide luminescent material of the present invention, the method steps are as follows:

[0010] (1) Tetraphenylphosphonium bromide (C 24 H 20 PBr) powder, cuprous bromide (CuBr) powder and dimethyl sulfoxide (DMSO) were mixed evenly to form a brown-green turbid liquid to obtain precursor solution I;

[0011] Furthermore, the molar ratio of tetraphenylphosphine bromide to cuprous bromide is 1:1.5 to 1:2.5.

[0012] (2) When preparing a single crystal of the luminescent material:

[0013] Under stirring conditions, hypophosphorous acid (H3PO2) is added to the precursor solution I obtained in step (1) to obtain a clear and transparent precursor solution II; the precursor solution II is filtered, and then placed in an environment of -20 to -10°C, and allowed to stand for 2h to 10h to precipitate a single crystal, which is an orange-red copper-based halide luminescent material of the present invention;

[0014] Furthermore, the concentration of tetraphenylphosphonium bromide in dimethyl sulfoxide is 0.2 mol / L to 0.5 mol / L.

[0015] Furthermore, during the preparation of the precursor solution II, the stirring rate is 300 r / min to 500 r / min.

[0016] Furthermore, the precursor solution II is filtered using a filter head with a pore size of 0.2 μm to 0.5 μm.

[0017] When preparing the micron crystals of the luminescent material:

[0018] Under vigorous stirring, anti-solvent hypophosphorous acid is added dropwise to the precursor solution I obtained in step (1), and the brown-green turbid liquid is observed to first become clear and transparent, and then a white precipitate is generated. The white precipitate is collected by filtration and dried to obtain micron crystals, which are an orange-red copper-based halide luminescent material according to the present invention;

[0019] Furthermore, the concentration of tetraphenylphosphonium bromide in dimethyl sulfoxide is 0.4 mol / L to 0.6 mol / L.

[0020] Further, hypophosphorous acid is added dropwise to the precursor solution I at a rate of 0.1 mL / min to 0.5 mL / min at a stirring rate of 800 r / min to 1200 r / min.

[0021] Beneficial Effects

[0022] (1) The present invention provides an orange-red copper-based halide luminescent material, wherein the molecular formula of the luminescent material is (TPP)2Cu4Br6·2DMSO, and the luminescent material is a zero-dimensional non-lead copper-based organic-inorganic hybrid metal halide, belonging to the Pbcn space group in the orthorhombic crystal system, with a band gap of 2.92 eV, an excitation spectrum with a peak wavelength at 370 nm, an emission spectrum showing a broadband emission with a peak wavelength at 615 nm, a FWHM of 126 nm, a fluorescence lifetime of 20.75 μs, a fluorescence quantum yield of 88.1%, and broadband orange-red light emission under ultraviolet excitation.

[0023] (2) The present invention provides an orange-red copper-based halide luminescent material. The luminescent material adopts a lead-free system, is non-toxic, and has the characteristics of low cost, high fluorescence quantum yield, and stable optical properties. It can emit bright orange-red light after ultraviolet excitation and shows great application prospects in the fields of optoelectronic devices and solid-state lighting.

[0024] (3) The present invention provides a method for preparing an orange-red copper-based halide luminescent material. The single crystal material of the luminescent material can be prepared by a low-temperature cooling crystallization method; the micron crystal material of the luminescent material can be prepared by an anti-solvent method at room temperature; the method does not require an environment such as high temperature and high pressure, the production conditions are mild, and it has the characteristics of simple operation, easy implementation, short reaction time, and large-scale preparation, which is conducive to the promotion and application of the luminescent material.

[0025] (4) The present invention provides a method for preparing an orange-red copper-based halide luminescent material. The method can prepare micron-crystalline materials of the luminescent material in large quantities by using an anti-solvent method at room temperature. Compared with rare earth metals, the metallic copper used in the present invention has abundant reserves and a lower price, and is more suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of the crystal and unit cell structure of the luminescent material prepared in Example 1.

[0027] Figure 2 The simulated single crystal X-ray diffraction (SCXRD) spectrum of the luminescent material prepared in Example 1 and the powder X-ray diffraction (PXRD) spectrum of the luminescent material prepared in Example 3 are shown in FIG.

[0028] Figure 3 These are the fluorescence excitation spectrum and emission spectrum of the luminescent material prepared in Example 3.

[0029] Figure 4 This is a graph of the fluorescence quantum yield of the luminescent material prepared in Example 3.

[0030] Figure 5 This is the EDS spectrum and element content of the luminescent material prepared in Example 3.

[0031] Figure 6 The time-resolved PL decay curve (points) of the luminescent material prepared in Example 4 and its single exponential fitting curve (line). DETAILED DESCRIPTION

[0032] The present invention is further described below in conjunction with specific embodiments, wherein the methods are conventional methods unless otherwise specified, and the raw materials can be obtained from public commercial channels unless otherwise specified.

[0033] Example 1

[0034] (1) Weigh 0.2 mmol (0.0839 g) of tetraphenylphosphine bromide powder and 0.3 mmol (0.0430 g) of cuprous bromide powder, place them in a 5 mL glass bottle, add 1 mL of dimethyl sulfoxide and mix well to form a brown-green turbid liquid, thereby obtaining a precursor solution I.

[0035] (2) Under stirring conditions at a stirring rate of 500 r / min, 100 μL of hypophosphorous acid is added to the precursor solution I obtained in step (1) to obtain a clear and transparent precursor solution II; the precursor solution II is filtered using a polytetrafluoroethylene filter with a pore size of 0.2 μm, and the resulting filtrate is placed at -10°C for 10 hours to precipitate a transparent single crystal, which is an orange-red copper-based halide luminescent material.

[0036] The luminescent material prepared in this embodiment was tested as follows:

[0037] (1) Single crystal analysis test - Instrument: single crystal X-ray diffractometer.

[0038] The results of single crystal analysis show that the prepared luminescent material is (TPP)2Cu4Br6·2DMSO single crystal, the crystal structure belongs to the orthorhombic system Pbcn, and the unit cell parameters are like Figure 1 As shown, [Cu4Br6] 2- The clusters are surrounded by large organic cations TPP + and DMSO molecules, forming a zero-dimensional electronic structure.

[0039] (2) X-ray diffraction test - Instrument: XtaLAB Synergy single crystal X-ray diffractometer.

[0040] The test results of single crystal simulation are as follows Figure 2 As shown in the upper curve in the figure, the XRD pattern of the powder sample prepared later is Figure 2 The diffraction patterns shown in the lower middle curve match each other, indicating the successful preparation of the target product.

[0041] (3) Luminous performance test - Instrument: portable UV lamp; Model: ZF-5; Manufacturer: Shanghai Jiapeng Technology.

[0042] The prepared luminescent material emits bright orange-red light when observed with the naked eye after being excited by a 370nm ultraviolet lamp.

[0043] Example 2

[0044] (1) Weigh 0.5 mmol (0.2096 g) of tetraphenylphosphine bromide powder and 1.25 mmol (0.1793 g) of cuprous bromide powder, place them in a 5 mL glass bottle, add 1 mL of dimethyl sulfoxide and mix well to form a brown-green turbid liquid, thereby obtaining precursor solution I.

[0045] (2) Under stirring conditions at a stirring rate of 300 r / min, 200 μL of hypophosphorous acid is added to the precursor solution I obtained in step (1) to obtain a clear and transparent precursor solution II; the precursor solution II is filtered using a polytetrafluoroethylene filter head with a pore size of 0.5 μm, and the resulting filtrate is placed at -20°C for 2 hours to precipitate a transparent crystalline single crystal, which is an orange-red copper-based halide luminescent material.

[0046] The luminescent material prepared in this embodiment was tested as follows:

[0047] (1) Single crystal analysis test - Instrument: single crystal X-ray diffractometer.

[0048] The test results of single crystal analysis show that the prepared luminescent material is (TPP)2Cu4Br6·2DMSO single crystal, and the crystal structure belongs to the orthorhombic system Pbcn, [Cu4Br6] 2- The unit is a large organic cation TPP + and DMSO molecules, forming a zero-dimensional electronic structure.

[0049] (2) Luminous performance test - Instrument: portable UV lamp; Model: ZF-5; Manufacturer: Shanghai Jiapeng Technology.

[0050] The prepared luminescent material emits bright orange-red light when observed with the naked eye after being excited by a 370nm ultraviolet lamp.

[0051] (3) Steady-state photoluminescence (PL) excitation (PLE) spectrum test - Instrument: Steady-state / transient fluorescence spectrometer FLS-1000.

[0052] The test results show that the peak wavelength of the excitation spectrum of the prepared luminescent material is at 370nm, and the emission spectrum exhibits a broadband emission characteristic with a peak wavelength at 615nm.

[0053] Example 3

[0054] (1) Weigh 0.4 mmol (0.1677 g) of tetraphenylphosphine bromide powder and 0.6 mmol (0.0861 g) of cuprous bromide powder, place them in a 5 mL glass bottle, add 1 mL of dimethyl sulfoxide and mix well to form a brown-green turbid liquid, thereby obtaining a precursor solution I.

[0055] (2) Under a stirring rate of 800 r / min, 300 μL of hypophosphorous acid was dropwise added to the precursor solution I prepared in step (1) at a rate of 0.1 mL / min, and the brown-green turbid liquid first became clear and transparent, and then a white precipitate appeared, indicating the formation of micron-crystalline (TPP)2Cu4Br6·2DMSO; the precursor solution was filtered using a PVDF filter membrane to quickly separate the powder from the liquid, and the solution was naturally dried to collect a powder sample, which was an orange-red copper-based halide luminescent material.

[0056] The luminescent material prepared in this embodiment was tested as follows:

[0057] (1) X-ray diffraction (XRD) test—Instrument: Bruker AXSD8 X-ray diffractometer.

[0058] according to Figure 2 The powder XRD test results shown in the middle and lower curves show that the prepared luminescent material is (TPP)2Cu4Br6·2DMSO micron crystals with high crystallinity. Figure 2 The diffraction pattern of the single crystal simulated XRD shown in the upper middle curve matches that of the single crystal, indicating that the micron-crystalline material is successfully prepared and that the material has a pure phase crystal structure.

[0059] (2) Steady-state photoluminescence (PL) and excitation (PLE) spectrum test - Instrument: Steady-state / transient fluorescence spectrometer FLS-1000.

[0060] The test results are as follows Figure 3 As shown, the peak wavelength of the excitation spectrum of the prepared luminescent material is at 370 nm, and the emission spectrum presents a broadband emission characteristic with a peak wavelength at 615 nm, a FWHM of about 126 nm, and a Stokes shift of 245 nm.

[0061] (3) Photoluminescence quantum yield (PLQY) test - Instrument: Quantaurus-QY quantum yield meter.

[0062] Test results such as Figure 4 As shown, the quantum yield of the prepared luminescent material under 370nm excitation reaches 88.1%.

[0063] (4) Energy dispersive X-ray spectroscopy (EDS) test - Instrument: scanning electron microscope.

[0064] EDS energy spectrum scanning analysis results are as follows Figure 5 As shown, the mass fractions of Cu, Br, P and S elements in the prepared luminescent material are 32.33%, 56.30%, 5.33% and 6.05%, respectively, and the corresponding molar ratios are 2.19:3.02:0.74:0.81, which are very close to the theoretical molar ratio of 2:3:1:1 of the chemical formula of the prepared luminescent material, further verifying the stoichiometric ratio of the prepared luminescent material.

[0065] (5) Luminous performance test - Instrument: portable UV lamp; Model: ZF-5; Manufacturer: Shanghai Jiapeng Technology.

[0066] The prepared luminescent material emits bright orange-red light when observed with the naked eye after being excited by a 370nm ultraviolet lamp.

[0067] Example 4

[0068] (1) Weigh 0.6 mmol (0.2516 g) of tetraphenylphosphine bromide powder and 1.5 mmol (0.2152 g) of cuprous bromide powder, place them in a 5 mL glass bottle, add 1 mL of dimethyl sulfoxide and mix well to form a brown-green turbid liquid, thereby obtaining precursor solution I.

[0069] (2) Under a stirring rate of 1200 r / min, 500 μL of hypophosphorous acid was dropwise added to the precursor solution I prepared in step (1) at a rate of 0.5 mL / min, and the brown-green turbid liquid first became clear and transparent, and then a white precipitate appeared, indicating the formation of micron-crystalline (TPP)2Cu4Br6·2DMSO; the precursor solution was filtered using a PVDF filter membrane to quickly separate the powder from the liquid, and the solution was naturally dried to collect a powder sample, which was an orange-red copper-based halide luminescent material.

[0070] The luminescent material prepared in this embodiment was tested as follows:

[0071] (1) X-ray diffraction (XRD) test—Instrument: Bruker AXSD8 X-ray diffractometer.

[0072] According to the powder XRD test results, the prepared luminescent material is (TPP)2Cu4Br6·2DMSO micron crystal with high crystallinity and pure phase crystal structure.

[0073] (2) Steady-state photoluminescence (PL) and excitation (PLE) spectrum test - Instrument: Steady-state / transient fluorescence spectrometer FLS-1000.

[0074] The test results show that the peak wavelength of the excitation spectrum of the prepared luminescent material is at 370nm, and the emission spectrum presents a broadband emission characteristic with a peak wavelength at 615nm, its FWHM is about 126nm, and the Stokes shift is 245nm.

[0075] (3) Photoluminescence quantum yield (PLQY) test - Instrument: Quantaurus-QY quantum yield meter.

[0076] The test results show that the quantum yield of the prepared luminescent material under 370nm excitation reaches 88.1%.

[0077] (4) Energy dispersive X-ray spectroscopy (EDS) test - Instrument: scanning electron microscope.

[0078] The test results show that the mass fractions of Cu, Br, P and S elements in the prepared luminescent materials are 32.33%, 56.30%, 5.33% and 6.05%, respectively. The corresponding molar ratios are 2.19:3.02:0.74:0.81, which are very close to the theoretical molar ratio of 2:3:1:1 of the chemical formula of the prepared luminescent material, further verifying the stoichiometric ratio of the prepared luminescent material.

[0079] (5) Luminous performance test - Instrument: portable UV lamp; Model: ZF-5; Manufacturer: Shanghai Jiapeng Technology.

[0080] The prepared luminescent material emits bright orange-red light when observed with the naked eye after being excited by a 370nm ultraviolet lamp.

[0081] (6) Fluorescence lifetime test - Instrument: Steady-state / transient fluorescence spectrometer.

[0082] The time-resolved fluorescence decay test results are as follows Figure 6 As shown, the time-resolved fluorescence spectrum of the prepared luminescent material monitored at 615 nm under room temperature exhibits a single exponential decay and has a lifetime of up to 20.75 μs.

[0083] In summary, the above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An orange-red copper-based halide luminescent material, characterized in that: The molecular formula of the luminescent material is (TPP)2Cu4Br6·2DMSO.

2. An orange-red copper-based halide luminescent material according to claim 1, characterized in that: The luminescent material belongs to the Pbcn space group in the orthorhombic crystal system and exhibits broadband orange-red light emission under ultraviolet excitation.

3. A method for preparing the orange-red copper-based halide luminescent material according to claim 1 or 2, characterized in that: (1) Tetraphenylphosphonium bromide powder, cuprous bromide powder and dimethyl sulfoxide are uniformly mixed to obtain a precursor solution I; (2) When preparing a single crystal of the luminescent material: Under stirring conditions, hypophosphorous acid is added to the precursor solution I to obtain a clear and transparent precursor solution II; The precursor solution II is filtered, and then placed at -20 to -10°C for 2 to 10 hours to precipitate a single crystal, which is an orange-red copper-based halide luminescent material; When preparing the micron crystals of the luminescent material: Under stirring conditions, hypophosphorous acid was added dropwise to the precursor solution I. It was observed that the brown-green turbid liquid first became clear and transparent, and then a white precipitate was generated. The white precipitate was collected by filtration and dried to obtain micron crystals, which are an orange-red copper-based halide luminescent material.

4. The method for preparing an orange-red copper-based halide luminescent material according to claim 3, characterized in that: The molar ratio of tetraphenylphosphonium bromide to cuprous bromide is 1:1.5 to 1:2.

5.

5. The method for preparing an orange-red copper-based halide luminescent material according to claim 3 or 4, characterized in that: When preparing a single crystal of the luminescent material, the concentration of tetraphenylphosphonium bromide in dimethyl sulfoxide is 0.2 mol / L to 0.5 mol / L; When preparing the micron crystals of the luminescent material, the concentration of tetraphenylphosphonium bromide in dimethyl sulfoxide is 0.4 mol / L to 0.6 mol / L.

6. The method for preparing an orange-red copper-based halide luminescent material according to claim 3 or 4, characterized in that: When preparing the single crystal of the luminescent material, the stirring rate during the preparation of the precursor solution II is 300 r / min to 500 r / min.

7. The method for preparing an orange-red copper-based halide luminescent material according to claim 3 or 4, characterized in that: When preparing the single crystal of the luminescent material, the precursor solution II is filtered using a filter head with a pore size of 0.2 μm to 0.5 μm.

8. The method for preparing an orange-red copper-based halide luminescent material according to claim 3 or 4, characterized in that: When preparing the micron crystals of the luminescent material, hypophosphorous acid is added dropwise to the precursor solution I at a rate of 0.1 mL / min to 0.5 mL / min at a stirring rate of 800 r / min to 1200 r / min.

Citation Information

Cited By

  • Organic-inorganic hybrid copper-based halide luminescent material as well as preparation method and application thereof

    CN122541372A